Pembangunan Daerah dan Desa Serta Pemberdayaan Keluarga (Posdaya) Guna Tercapainya Peningkatan Kesempatan Kerja dan Percepatan Penurunan Kemiskinan - Hasibuan, Afriadi Sjahbana (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2016)
Decentralization and Regional Autonomy have been running for almost two decades in the unitary Republic of Indonesia (Negara Kesatuan Republik Indonesia = NKRI). In the course of nearly two decades, the local goverment system is basic undergone changes from one Act to another Act, which makes the foundation of the implementation of the the decentralization and regional autonomy. In addition, Act No. 6 of Year 2014 aboout The Village also experienced several changes, the latter is giving new hope to people with the recognition of rural and indigenous villages. Public expectations with the bird of the Act is the references for the work of the Act is the reference for the work of local goverment and village can open up job opportunites ti accelerate the reduction of poverty. Therefore, Act No. 23 of 2014 on Regional Goverment and Law No. 6 of 2014 on Village Goverment to respond to the interest of society provide businees with the regional goverment affairs have 32 well obligatory, as well as business together (concurrent). Likewise, the village is given an assignment by the Government to take care of the village administration, rural development, and community empowerment and social development (Article 22). 32nd affairs and village assignment is managed and implemented effectively throught the mechanism of regional and rural development managementfor the benefit of society. Giving affairs and the assignment is meant to be able to open up employment opportunities and accelerating provety reduction in the Region to improve intelligence and prosperity to the region's autonomy (visionary). To achieve it implemented empowerment by giving understanding and preparation of visionary organizations (Local Goverment) to get an increase in perfomance is vandalism economic resources locally effective namely diggging and manage based on local resources itself by providing a foundation of knowledge to the community to have to professionalism, competence and has to ability to innovate on local economic resources toward regional cometitiveness aimed at open and compete to penetratae global market.